2t+3(t-4)=6-2(3t-2)

Simple and best practice solution for 2t+3(t-4)=6-2(3t-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2t+3(t-4)=6-2(3t-2) equation:



2t+3(t-4)=6-2(3t-2)
We move all terms to the left:
2t+3(t-4)-(6-2(3t-2))=0
We multiply parentheses
2t+3t-(6-2(3t-2))-12=0
We calculate terms in parentheses: -(6-2(3t-2)), so:
6-2(3t-2)
determiningTheFunctionDomain -2(3t-2)+6
We multiply parentheses
-6t+4+6
We add all the numbers together, and all the variables
-6t+10
Back to the equation:
-(-6t+10)
We add all the numbers together, and all the variables
5t-(-6t+10)-12=0
We get rid of parentheses
5t+6t-10-12=0
We add all the numbers together, and all the variables
11t-22=0
We move all terms containing t to the left, all other terms to the right
11t=22
t=22/11
t=2

See similar equations:

| 3(x-8)=-2x+7(6-1) | | 10n+-4=94 | | 4(w-6)=3(+1 | | -2(6x-3)=3(x+4) | | -15.9u+19.64=-8.36-18.7u | | 5(2x+5)=-21+26 | | -6b-b=-8b+2b+4 | | 6x-12+3x=5+9x-17 | | X²-2x+56=0 | | -7/16w-26=19 | | 5.8=–4.5+z | | -9/5=3x | | 6n+5=42 | | 5x+13+2x+8=84 | | 8x-16=7x+28 | | 8x-18=24 | | (0)+y=9 | | 2.2x-6.2-34=-6 | | -20+2g=20-10g+20 | | 4x+0.4=4.4 | | (n-31)/4=2 | | 15y-10y=46.90 | | -31=(6)-10-2w | | 10-4x=-5x+6 | | 9x-5-4x=-25 | | 24+14x=-6x+24 | | -13d-8=-2(d+4)-11d | | 10n-15=14n+9 | | 15=10+9.8t | | 7x-1-5x+8=13 | | 6)-31=-10-2w | | F(2)=6x-4 |

Equations solver categories